1999
DOI: 10.1029/1999ja900055
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on theories of Pc1 pearl formation

Abstract: Abstract. In this paper we study structured Pcl pulsations (also called Pcl pearls) observed on ground, concentrating on the relation between the pearl repetition period •-and the wave frequency f. Earlier studies suggest that the product •-f is roughly constant. We reexamine this relation and show that a simple inverse law is excluded. Instead, our observations suggest the relation •-c• f-P, with p -0.59 4-0.06, posing a new, strict constraint on theories of Pc1 pearl formation. We also study the L dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This model suggests that Pc1 pearl structures are caused by the bouncing of Pc1 waves along the geomagnetic field lines, between the northern and southern hemispheres. Mursula et al (1999) found that there was a strong negative correlation between the repetition period of Pc1 pearl structures and the frequency of Pc1 pulsations. They implied that the L-shell dependence of various Pc1 frequencies, and the repetition period of Pc1 pearl structures may be interpreted by the BWP model.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This model suggests that Pc1 pearl structures are caused by the bouncing of Pc1 waves along the geomagnetic field lines, between the northern and southern hemispheres. Mursula et al (1999) found that there was a strong negative correlation between the repetition period of Pc1 pearl structures and the frequency of Pc1 pulsations. They implied that the L-shell dependence of various Pc1 frequencies, and the repetition period of Pc1 pearl structures may be interpreted by the BWP model.…”
Section: Introductionmentioning
confidence: 95%
“…One of the possible generation mechanisms is based on the BWP model (e.g., Guglielmi et al (1996);Mursula et al (1999)). This model explains that Pc1 pearl structures are caused by bouncing of Pc1 waves along the geomagnetic field line between the northern and southern hemispheres.…”
Section: Possible Generation Mechanisms Of Pc1 Pearl Structures In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature, including dozens of reviews and monographs, has been accumulated in 70 years of experimental and theoretical investigations of the Pc1 waves (e.g., Troitskaya, 1964;Troitskaya andGuglielmi, 1967, 1969;Saito, 1969;Guglielmi and Troitskaya 1973;Guglielmi, 1974Guglielmi, , 1979Guglielmi, , 1989Gendrin, 1975;Nishida, 1978;Fraser, 1985;Anderson et al, 1992a, b;Pokhotelov, 1994, 1996;Kangas et al, 1998Kangas et al, , 1999 and lively discussions about the Pc1 origin and properties still continue (e.g., Johnson and Cheng, 1999;Mursula et al, 1999Mursula et al, , 2001Guglielmi et al, 2001;Loto'aniu et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…They are sensitive to changes in dynamics and structure of the magnetosphere. These emissions have great diagnostic potential, providing insight into various magnetospheric processes as well as numerical estimates of key parameters of the medium [Guglielmi et al, 1972;Matveeva et al, 1972;Guglielmi, Troitskaya, 1973;Mursula et al, 1999]. This generally concerns the pearls observed under quiet and moderately disturbed conditions.…”
mentioning
confidence: 99%